Trend Analysis of Clinical Characteristics of COVID-19 with Diabetes Based on Disease Severity - Batari Retno Minanti; Soebagijo Adi Soelistijo; Agung Pranoto (PP PERKENI, 2024)
Diabetes Mellitus (DM) increases the risk of COVID-19's severity and mortality than those without DM. The aim of this study was to determine the characteristics and trends by disease severity of DM patients with COVID-19. Across-sectional study examining retrospective medical records was conducted in patients with diabetes mellitus who were confirmed to have COVID-19 by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). All adult patients (age > 18 years) with DM and COVID-19 registered and treated at the Surabaya Hajj General Hospital from May 2021 to the end of December 2021 were included in this study. Trends in each subject's characteristics are displayed in a graph with a trendline based on the severity of COVID-19. The highest proportionof disease severity of DM patients with COVID-19 is mild and moderate cases (72.2%), with 27.8% severe and critical cases. The average aged of the subjects was 56.38 ± 9.60 years. The age group with the highest proportion was 50-59 (42.6%). There are slightly more female than male patients (50.4% vs. 49.6%). The tendency is that the disease's severity increases with BMI, increasing HbA1C level, low sodium level, high chloride level, and high CRP and D-dimer levels. The pattern of clinical and laboratory features of DM patients based on the severity of COVID-19 infection shows the tendency for the disease severity worsens with increasing BMI, HbA1C level, low sodium level, high chloride level, and high CRP and D- dimer levels.